Spearman and Pearson Correlation Tests: Analyzing Negative and CAR Correlation in Indonesian Islamic Finance (2021-2023) - Widodo, Prima Ariyo; Isman, I; Hidayat, Syamsul; Risdayani, R (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study examines the correlation between Non-Performing Financing (NPF) and Capital Adequacy Ratio (CAR) in Indonesian Islamic finance from 2021 to 2023. The study employed Pearson and Spearman correlation tests to examine the correlation between NPF and CAR in Indonesian Islamic finance from 2021 to 2023. The significance was determined by Sig. (2-tailed) values (p < 0.05), accepting H0 and rejecting H1. The Pearson (r) and Spearman (ρ) coefficients indicated a strong negative correlation. The robust methodology reinforces the findings on the intricate dynamics between NPF and CAR in the specified financial data. The findings, obtained through Pearson and Spearman correlation tests, reveal a significant negative correlation (p < 0.05), indicating an inversely proportional relationship. The strong negative correlation suggests that as NPF increases, CAR decreases, and vice versa. The study provides valuable insights into the dynamic interplay between NPF and CAR in Islamic financial data.